log(x-1)-log(x-2)=log(x-2)

Simple and best practice solution for log(x-1)-log(x-2)=log(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x-1)-log(x-2)=log(x-2) equation:


Simplifying
log(x + -1) + -1log(x + -2) = log(x + -2)

Reorder the terms:
glo(-1 + x) + -1log(x + -2) = log(x + -2)
(-1 * glo + x * glo) + -1log(x + -2) = log(x + -2)
(-1glo + glox) + -1log(x + -2) = log(x + -2)

Reorder the terms:
-1glo + glox + -1glo(-2 + x) = log(x + -2)
-1glo + glox + (-2 * -1glo + x * -1glo) = log(x + -2)
-1glo + glox + (2glo + -1glox) = log(x + -2)

Reorder the terms:
-1glo + 2glo + glox + -1glox = log(x + -2)

Combine like terms: -1glo + 2glo = 1glo
1glo + glox + -1glox = log(x + -2)

Combine like terms: glox + -1glox = 0
1glo + 0 = log(x + -2)
1glo = log(x + -2)

Reorder the terms:
1glo = glo(-2 + x)
1glo = (-2 * glo + x * glo)
1glo = (-2glo + glox)

Solving
1glo = -2glo + glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '2glo' to each side of the equation.
1glo + 2glo = -2glo + 2glo + glox

Combine like terms: 1glo + 2glo = 3glo
3glo = -2glo + 2glo + glox

Combine like terms: -2glo + 2glo = 0
3glo = 0 + glox
3glo = glox

Add '-1glox' to each side of the equation.
3glo + -1glox = glox + -1glox

Combine like terms: glox + -1glox = 0
3glo + -1glox = 0

Factor out the Greatest Common Factor (GCF), 'glo'.
glo(3 + -1x) = 0

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing g to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -17=4(y-8)-7y | | 5x2/9 | | 7(3x^2-8)-[5(3x^2-4)+2]= | | 6x-5[2-(8-3x)]= | | 5-3[3-(5y-5)]= | | x^3-10x^2+32x-32= | | 8n+39=39 | | F(-1)=3x^2+2x-4 | | x^2-7x-73=0 | | -10y-6y= | | 5(-4y-15)= | | 2*6-1.5y+3*0=12 | | 3c+2b+2c+4b= | | 2(6-1.5y)+(3*0)=12 | | 5-10y-15-6y= | | 215=(1/2)9.8t^2 | | x-0.15x=300 | | 5x+25=3x+(-5) | | x-6.9=-9.9 | | 8d(2d+3e)= | | 1000x+17x=5 | | 2y(x+y+z)dx+(y^2-x^2-4x-1)dy=0 | | 3(2x-5)+5(x-6)=1 | | 120/8=x/15 | | 5c-6=4+3c | | 0=sin(24x) | | 2x(4+6)=4x-8 | | 11/x=22/x-4 | | 3y+x-7=0 | | h(18430)=220+0.04(18430-9000) | | 3(-6x+1)-5x=72 | | 1762=598+24.25n |

Equations solver categories